Effects of perceived social support on maternal stress and breastfeeding: A narrative review - Sosa Paez, Valeria Paola; Kamenetzky, Giselle; Rovella, Anna (Interacciones, 2023)
Background: Health authorities recommend exclusive breastfeeding until six months of age and continued breastfeeding (BF) until two years. Objective: To conduct a narrative review of the effects of social support on maternal distress and BF. Method: A narrative and non-systematic review was conducted, selecting articles from the literature in PubMed, Redalyc, BVS, and from websites of organisations such as WHO and UNICEF. Results: The results show that low social support is associated with increased maternal stress and affects the initiation and maintenance of breastfeeding. Social support acts to reduce stress levels. Conclusion: Social support is a factor to be considered as a strategy to reduce maternal stress and promote BF. It is necessary to emphasise the role of healthcare teams in promoting BF, especially among single-parent mothers, by providing social support and breastfeeding education.